Use of in situ simulation to evaluate the operational readiness of a high‐consequence infectious disease intensive care unit. (30th March 2020) - Fregene, T. E.; Nadarajah, P.; Buckley, J. F.; Bigham, S.; Nangalia, V.
Summary: On 30 January 2020, the World Health Organization (WHO) declared that the outbreak of a coronavirus disease‐2019 (COVID‐19) was a public health emergency of international concern. The WHO guidance states that patients with (COVID‐19) should be managed by staff wearing appropriate personal protective equipment; however, working whilst wearing personal protective equipment is unfamiliar to many healthcare professionals. We ran high‐fidelity, in‐situ simulation of high‐risk procedures on patients with COVID‐19 in a negative‐pressure side room on our intensive care unit (ICU). Our aim was to identify potential problems, test the robustness of our systems and inform modification of our standard operating procedures for any patients with COVID‐19 admitted to our ICU. The simulations revealed several important latent risks and allowed us to put corrective measures in place before the admission of patients with COVID‐19. We recommend that staff working in clinical areas expected to receive patients with COVID‐19 conduct in‐situ simulation in order to detect their own unique risks and aid in the creation of local guidelines of management of patients with COVID‐19.